Preparation and Characterization of TiO2-LaFeO3 based Mixed Matrix Membrane for Oily Wastewater Treatment - Patrick, R.; Aziz, F.; Yahya, N.; Jamaludin, N. A.; Ismail, N. M. (Journal of Applied Membrane Science & Technology, 2017)
The aim of this study was to investigate the effects of catalyst loading in mixed matrix membrane. LaFeO3 and TiO2-LaFeO3 were synthesized by sol-gel glucose method. Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), contact angle, membrane permeation testing unit and UV-Vis spectrophotometer techniques are used for characterization. FTIR showed the successful transformation of photocatalyst TiO2, LaFeO3 and TiO2-LaFeO3. Due to increase in nanoparticles loading, the hydrophilicity of the membrane had improved thus increase the permeation flux. The cross-section morphology of membranes (PTL-1, PTL-3 and PTL-4) indicated that all the membranes were found to have asymmetric structure, consisting of dense top layer (air side), a porous sublayer (finger-like) and a small portion of sponge-like bottom surface layer (glass side). But as for the PTL-2, the cross sections of the membranes have a fully sponge-like structure. The formation of sponge-like structure was associated to the slow solidification process during the casting. The highest oily wastewater rejection was 76.26% with highest permeation flux and lower contact angle. This result showed that nanoparticles with membrane had improved the oily wastewater rejection. It proved that the fabricated nanoparticles with mixed matrix membrane exhibits a high flux, which is 2 to 3 orders of magnitude higher than commercial filtration membranes with an acceptable separation performance.